Present limits to cosmic bubbles from the COBE-DMR three-point correlation function - Corasaniti, Pier Stefano; Amendola, Luca; Occhionero, Franco (Monthly notices of the Royal Astronomical Society, 2001)
The existence of large-scale voids in several galaxy surveys suggests the occurrence of an inflationary first-order phase transition. This process generates primordial bubbles that, before evolving into the present voids, leave at decoupling a non-Gaussian imprint on the cosmic microwave background.In this paper we evaluate an analytical expression of the collapsed three-point correlation function from the bubble temperature fluctuations. Comparing the results with COBE-DMR measures, we obtain upper limits on the allowed non-Gaussianity and hence on the bubble parameters.